What Have Advances in Transcriptomic Technologies Taught us About Human White Matter Pathologies? - Jäkel, Sarah; Williams, Anna (Frontiers in Cellular Neuroscience, 2020)
For a long time, post-mortem analysis of human brain pathologies has been purely descriptive, limiting insight into the pathological mechanisms. However, starting in the early 2000’s, next generation sequencing and the routine application of bulk RNA-sequencing and microarray technologies has revolutionized the usefulness of post-mortem human brain tissue. This has allowed many studies to provide novel mechanistic insights into certain brain pathologies, albeit at a still unsatisfying resolution, with masking of lowly expressed genes and of regulatory elements in different cell types. The recent rapid evolution of single cell technologies has now allowed researchers to shed light on human pathologies at a previously unreached resolution revealing further insights into pathological mechanisms that will open the way for development of new strategies for therapies. In this review, we will give an overview of the incremental information that single cell technologies have given us for human white matter pathologies, summarize which single cell technologies are available and speculate where these novel approaches may lead us for pathological assessment in the future.